Malignant teratoma of the thyroid. Issue 7 (28th July 2021) - Bidaye, Rohan; Mahmood, Ashraf; Abdawn, Zainab; Ahmad, Ijaz
Abstract : Malignant thyroid teratoma in adults is a rare tumour with less than 40 cases reported worldwide. Our case is of a 29-year-old man who presented with a thyroid lump and compressive symptoms. He underwent multiple investigations before being diagnosed with a malignant thyroid teratoma. There are no established guidelines in the management of this tumour yet. In this case report, we discuss the diagnosis, treatment and follow-up of the patient and reflect on the published literature on this tumour.